The ghost shift : a novel - Gapper, John (Ballantine Books, 2015)
"In the tradition of Gorky Park, John Gapper's new thriller takes readers inside the secretive and dangerous world of modern China, as a young woman makes a haunting discovery--one that forces her to choose between duty to her government and a desperate desire to learn the truth about herself. This wasn't just a body in a field. The corpse's shape was hers--same length, same curves. Then she knew, and everything else receded to nothingness. All she could see was a woman with the same nose, the same eyes, and the same face. Her twin. As an up-and-coming agent of the Commission for Discipline Inspection, Song Mei probes political corruption, not mysterious deaths. But that changes when she arrives on the scene of a grim police investigation and is confronted with a crime--and a victim--impossible to ignore. Despite strict orders and even threats from superiors, Mei knows there can be no turning away. Breaking protocol, Mei undertakes a covert search for the truth about the mystery woman's death--and life--by following in her footsteps from a factory plagued by worker suicides to a luxury hotel dealing in high-end escorts to an American home haunted by tragedy. But when Mei crosses paths with an ex-CIA operative on a shadowy mission of his own, her personal quest takes a jarring turn into political and industrial espionage that pits both agents against the highest ranks of communism and capitalism. Praise for John Gapper's A Fatal Debt "Rarely does one read a first novel so self-assured, sharp, and compelling. It takes off like a rocket and doesn't stop until its explosive conclusion."--Joseph Finder, author of Suspicion "An enlightening and grisly tale. tightly plotted and fast-paced."--The New Yorker "An ingenious thriller about the ruthless world of high finance."--The Washington Post "A fast-paced book that should entertain finance aficionados and fans of detective fiction alike."--Fortune "A neatly crafted and well-written thriller. an audacious, assured debut."--David Ignatius, author of Bloodmoney "[Gapper] knows when to put his foot on the narrative accelerator."--Financial Times "Intriguing. suspenseful. a web of deceit and betrayal."--Booklist"--